Comparación de las estructuras de pavimento rígido y flexible por medio de un análisis de ciclo de vida, enfocado a carreteras de tránsito pesado - Coto-Sánchez, José David (Instituto Tecnológico de Costa Rica., 2016)
This project aims to perform a comparison between rigid pavement and flexible pavement, applied to the case of the recently completed road Cañas-Liberia, through a life cycle analysis. Within this analysis, the initial construction costs of each pavement structure is contemplated, as well as the activities required for their maintenance, also with its respective cost, during the design period considered. It is concluded that the rigid pavement is the best choice to build, according to the present conditions, because it has several advantages that cancel the difference obtained in the initial construction cost, compared to the flexible pavement.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Erosión de suelos; Construcción; Caminos; Infraestructura; Concreto; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Building engineering